Success for College Students with Learning Disabilities
XVIII, 360 p.
Keywords: JANET W. LERNER This timely volume explores issues pertinent to the emerging subject of college education for adults with learning disabilities. The inspiration for the book was a conference held at Barat College in Lake Forest Illinois on April 7, 1990, entitled College Students with Learning Disabilities: Reviewing the '80s and Planning for the '90s. The occasion was the celebration of the tenth anniversary of Barat College's program for college students with learning disabilities. Papers presented at this con ference, plus several additional invited chapters, and those of the co editors are included in this much needed publication. Only a few years ago, college was out of the question for most adults with learning disabilities. It is heartening to note that this situation has changed substantially over the last 15 or so years, with great strides in opportunities for adults with learning disabilities to acquire a college level education. From a slow beginning with programs such as the one at Barat College, there are today programs and support services in a variety of settings at a growing number of colleges and universities. Many indi viduals with learning disabilities can look forward to experiencing college and better preparing themselves for the future. The collection of papers in this book offers a comprehensive review of this exciting and challenging field.